Traditional Nusantara Dance as an Inspiration for Painted Batik Creations - Gagas Prakoso; Syakir, Syakir (Universitas Negeri Semarang, 2025)
This research discusses the development of painted batik inspired by traditional Nusantara dance as a creative foundation. The selection of the painted batik technique in this theme aims to combine two traditional art forms traditional dance and batik to create a unique fusion of cultural heritage. This study introduces novelty by highlighting various traditional Nusantara dances, such as the Legong Dance, Burung Enggang Dance, and Gambyong Dance, as sources of inspiration for painted batik creation. This enriches batik art by incorporating broader and more diverse cultural elements. The creation process includes conceptual stages, idea visualization through sketches and designs, and application on primisima mori fabric. Hand-drawn batik techniques and colet coloring are employed in producing seven painted batik artworks of varying sizes. The selected Nusantara dances include the Legong Dance, Burung Enggang Dance, Jaran Kepang Dance, Gambyong Dance, Topeng Klana Dance, Topeng Betawi Dance, and Merak Dance. Each artistic visualization in the painted batik reflects the movements, decorative patterns, philosophy, and meaning embedded in traditional dance. This research aims to produce artworks that offer novelty and innovation by visualizing traditional Nusantara dance in painted batik. The findings indicate that the visualization of traditional Nusantara dance in painted batik is successfully realized through the exploration of movement, decorative patterns, and the philosophy of each dance. The resulting works showcase the unique characteristics of each dance with an innovative aesthetic approach. Additionally, this research contributes to cultural preservation by introducing traditional dance through the medium of painted batik and enhancing public appreciation of traditional arts.